Antidiabetic antioxidant and phytochemical profile of yellow-fleshed seeded watermelon (Citrullus lanatus) extracts - Jibril, Muhammad Mustapha; Abdul-Hamid, Azizah; Mohd Ghazali, Hasanah; Pak Dek, Mohd Sabri; Ramli, Nurul Shazini; Jaafar, Ahmad Haniff; Karrupan, Jeevan; Mohammed, Abdulkarim Sabo (Science and Education Publishing, 2019)
Watermelon (Citrullus lanatus) consumption as shown by different studies is attributed to many health benefits, like in prevention of hypertension, cancer, cardiovascular diseases, and even type 2 diabetes due to its phytochemical constituents. The anti-diabetic effects of the seed, flesh, rind and leaf of yellow flesh watermelon extracts were evaluated through the inhibition of alpha-amylase and alpha-glucosidase enzymes activities by standard methods. The total phenolics content (TPC) and the total antioxidant capacities of the extracts were also evaluated using 2,2-azinobis (3-ethyl-benzothiazoline-6-sulfonic acid) (ABTS), ferric reducing antioxidant power (FRAP) and 2,2’-diphenyl-1,1-pycrylhydrazine (DPPH) assay methods. Metabolites of the 70% aqueous extract were profiled by liquid chromatographic mass spectrometry. Result of the study showed that the 70% aqueous ethanol flesh extract showed the highest α-amylase inhibition, followed by ethanol leaf extract. The 70% aqueous ethanol leaf extract had the highest α-glucosidase inhibition potential than the other studied extracts. The highest and lowest TPC were observed in 80% and 50% aqueous ethanol leaf and flesh extracts respectively. Ethanolic leaf extract showed the highest antioxidant activity in terms of FRAP, been higher than that of standard ascorbic acid. Based on ABTS radical scavenging and FRAP, 70% aqueous ethanol leaf extract had the highest antioxidant activity. The 90% aqueous ethanol gave the highest extraction yield for seed, 60% for flesh and rind, and 100% ethanol for leaf extract. Among the metabolites identified in watermelon extracts are curcumenol, curcubitacin E, citrulline, 6-gingerol, citric acid, ascorbic acid, leucine, arginine, palmitic acid, arjunolic acid, glucose, fructose, sucrose, naringenin 5,7-dimethyl ether 4'-O-xylosyl-(1->4)-arabinoside, 4'-apo-beta,psi-caroten-4'-al, caffeic acid 3-glucoside, luteolin 7-rhamnosyl (1->6) galactoside, apigenin 7-(4'',6''-diacetylalloside)-4'-alloside among others. Therefore, this result indicates that C. lanatus has antidiabetic and antioxidant potentials. The leaf having the best α-glucosidase inhibition ability and the best antioxidant potentials, could be regarded a good raw material to explore lead molecule(s) against diabetes mellitus and antioxidant.